2x + y = 1
3x - y = -6
---------------add
5x = -5
x = -5/5
x = -1
2(-1) + y = 1
-2 + y = 1
y = 1 + 2
y = 3
solution is (-1,3)
Answer:g(X)=2x^2-10
Step-by-step explanation:
If a function f(x) is translated 'c' units down then the equation of the translated function be f(x)-c
Here, f(x) is translated 2 units down to obtain g(x).
Hence, we have
g(x)=f(x)-2
=2x^2-8-2
=2x^2-10
Since 17 isnt a factor of 42 the only factor is 1
<u>CHECK </u><u>THE </u><u>TERMS </u><u>OF </u><u>USE.</u><u>.</u><u>. </u>
<u>UNDER </u><u>THAT, </u><u>YOU'LL </u><u>SEE </u><u>SUBSCRIPTIONS, </u><u>ETC.</u><u>.</u><u>. </u>
3x-24=x+10
3x-x=24+10
2x=34
x=34:2=17